Ti2AlNb / Ti-48Al-2Cr-2Nb composite material blade and preparation method thereof

By doping Ti2AlNb in Ti-48Al-2Cr-2Nb and using EBM forming process, Ti2AlNb/Ti-48Al-2Cr-2Nb composite blades were prepared, which solved the problems of difficult control of oxygen and nitrogen elements, large residual stress, poor surface quality and microstructure when preparing TiAl alloy blades in the prior art, and achieved efficient molding and excellent mechanical properties of the material.

CN119839313AActive Publication Date: 2025-04-18UNIV OF SCI & TECH BEIJING
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510191132.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-20
Publication Date
2025-04-18
Estimated Expiration
2045-02-20

AI Technical Summary

Technical Problem

The prior art has problems such as difficult to control oxygen and nitrogen elements, large residual stress, poor surface quality and microstructure when preparing TiAl alloy blades, especially in high temperature environments, the mechanical properties of the materials are insufficient.

Method used

Ti-48Al-2Cr-2Nb powder and Ti2AlNb powder were prepared by rotary electrode powdering method through the integrated control technology of the entire process oxygen content, and the Ti2AlNb powder was laid and melted layer by layer through the electron beam selection melting (EBM) forming process to form Ti2AlNb/Ti-48Al-2Cr-2Nb composite blades.

Benefits of technology

The precise molding of the material is achieved, the density of the blade, room temperature and high temperature tensile strength, yield strength and plastic properties are improved, and the problems of difficult control of oxygen and nitrogen elements, large residual stress, poor surface quality and microstructure are solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119839313A_ABST
    Figure CN119839313A_ABST
Patent Text Reader

Abstract

The invention provides a Ti2AlNb / Ti-48Al-2Cr-2Nb composite material blade and a preparation method of the Ti2AlNb / Ti-48Al-2Cr-2Nb composite material blade and belongs to the technical field of alloy material preparation. The preparation method comprises the following steps: respectively preparing Ti-48Al-2Cr-2Nb powder and Ti2AlNb powder by adopting a rotating electrode powder preparation method through a whole-process oxygen content integrated control technology; the preparation method comprises the following steps: uniformly mixing Ti-48Al-2Cr-2Nb powder and Ti2AlNb powder to form mixed powder; and an EBM forming technology is adopted, the mixed powder is flatly laid on a base plate layer by layer, the mixed powder is molten to form a printed blade workpiece in an electron beam layer-by-layer scanning mode, and the Ti2AlNb / Ti-48Al-2Cr-2Nb composite material blade is obtained. The Ti2AlNb powder and the Ti-48Al-2Cr-2Nb powder are doped, the Ti2AlNb / Ti-48Al-2Cr-2Nb composite material blade is obtained through the electron beam printing forming technology, and the high-temperature tensile strength and the yield strength of the blade are both better than those of an undoped sample.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of alloy material preparation, and in particular relates to a Ti2AlNb / Ti-48Al-2Cr-2Nb composite blade and a preparation method thereof. Background Art

[0002] With the continuous progress of the aviation industry, the working environment of aircraft engines has become increasingly complex, and higher requirements have been placed on the energy consumption, life and performance of aircraft engines. Among them, engine blades have very high requirements on the mechanical properties of materials, and are currently mainly made of high-temperature alloys, such as titanium aluminum alloys, nickel-based alloys, etc. Among them, TiAl alloys are expected to replace Ni-based alloys as materials for low-pressure turbine blades of aircraft engines in medium and high temperature (600-900℃) service environments due to their low density, high specific strength and specific modulus, and excellent high-temperature oxidation resistance, creep resistance and fatigue resistance.

[0003] However, TiAl alloys are brittle at room temperature, which leads to high processing difficulty, poor room temperature damage tolerance, and short life. These characteristics limit further engineering applications. Moreover, the structure and shape of engine blades are complex, and it is difficult to obtain fine full-lamellar structures by traditional forming methods. When using current technical means to form TiAl alloy blades, there are still problems to varying degrees. For example, TiAl alloy blades formed by laser melting deposition technology will have problems such as difficulty in controlling the O and N elements in the forming environment and large residual stress in the formed specimens; TiAl alloy blades formed by electron beam selective melting (EBM) additive manufacturing technology have poor surface quality and microstructure, and there are problems such as powder blowing, insufficient density, and Al element loss. In particular, when the sample surface is about 90° to the construction direction, different organizational morphologies will be presented along the forming direction, resulting in uneven organization, reduced mechanical properties, and poor room temperature plasticity. Summary of the invention

[0004] The present disclosure aims to solve at least one of the technical problems existing in the prior art and provides a Ti2AlNb / Ti-48Al-2Cr-2Nb composite blade and a preparation method thereof.

[0005] The present disclosure provides a method for preparing a Ti2AlNb / Ti-48Al-2Cr-2Nb composite blade, the preparation method comprising:

[0006] Ti-48Al-2Cr-2Nb powder and Ti2AlNb powder were prepared by rotating electrode powder making method through integrated control of oxygen content in the whole process;

[0007] The Ti-48Al-2Cr-2Nb powder and the Ti2AlNb powder are uniformly mixed to obtain a mixed powder;

[0008] The mixed powder is spread layer by layer on a substrate by adopting an EBM forming process, and the mixed powder is melted by electron beam scanning layer by layer to obtain a Ti2AlNb / Ti-48Al-2Cr-2Nb composite material blade.

[0009] Optionally, the oxygen content of the Ti-48Al-2Cr-2Nb powder and the Ti2AlNb powder is less than 700 ppm; and / or,

[0010] The Ti-48Al-2Cr-2Nb powder and the Ti2AlNb powder are spherical, and the particle size range is 15-150 μm.

[0011] Optionally, the mass ratio of the Ti2AlNb powder to the Ti-48Al-2Cr-2Nb powder is (10-30):(70-90).

[0012] Optionally, an EBM forming process is adopted to spread the mixed powder layer by layer on a substrate, and the mixed powder is melted by electron beam scanning layer by layer to obtain a Ti2AlNb / Ti-48Al-2Cr-2Nb composite blade, comprising:

[0013] The vacuum degree of the vacuum forming chamber should not exceed 5×10 -2 Pa, using electron beam to preheat the substrate and coat the mixed powder on the substrate;

[0014] The mixed powder is heated by an electron beam, and the printing temperature is controlled by temperature gradient control and real-time dynamic heat compensation. The mixed powder is selectively melted according to the cross-sectional information of the blade to form a cladding layer. The cladding layer is observed in real time to adjust the process of defective parts, and then the defect-free cladding layer is subjected to conformal heat treatment.

[0015] The mixed powder is clad layer by layer on the substrate repeatedly to form a printed workpiece, which is then further machined to obtain a Ti2AlNb / Ti-48Al-2Cr-2Nb blade.

[0016] Optionally, the preheating temperature of the substrate using an electron beam is 1000-1150° C. and the time is 10-30 minutes.

[0017] Optionally, in the process of melting the mixed powder by electron beam, the scanning path is 45°, the scanning path rotates 90° between each layer, the electron beam current is 12.5-14.5 mA, the scanning speed is 3.5-4.5 m / s, and the thickness of the mixed powder single layer cladding layer is 40-60

[0018] μm.

[0019] Optionally, the printing temperature is 1250-1350° C., and the printing time is 1-3 hours.

[0020] Optionally, the density of the Ti2AlNb / Ti-48Al-2Cr-2Nb composite material blade is 97.0-99.6%.

[0021] Optionally, the room temperature transverse tensile strength of the Ti2AlNb / Ti-48Al-2Cr-2Nb blade is 806-939.5 MPa, the room temperature longitudinal tensile strength is 695-790.1 MPa, the high temperature transverse tensile strength is 690-876.4 MPa, and the high temperature longitudinal tensile strength is 670-791.9 MPa.

[0022] In another aspect of the present disclosure, a Ti2AlNb / Ti-48Al-2Cr-2Nb composite material blade is provided. The Ti2AlNb / Ti-48Al-2Cr-2Nb composite material blade is prepared by the preparation method described above.

[0023] The present disclosure proposes a Ti2AlNb / Ti-48Al-2Cr-2Nb composite blade and a preparation method thereof. The preparation method comprises: using a rotating electrode powder making method to prepare Ti-48Al-2Cr-2Nb powder and Ti2AlNb powder respectively through a full-process oxygen content integrated control technology; mixing the Ti-48Al-2Cr-2Nb powder and the Ti2AlNb powder evenly to form a mixed powder; using an EBM forming process to spread the mixed powder layer by layer on a substrate, and melting the mixed powder by electron beam scanning layer by layer to obtain a Ti2AlNb / Ti-48Al-2Cr-2Nb composite blade. The present disclosure effectively fuses Ti2AlNb powder and Ti-48Al-2Cr-2Nb powder, and uses an EBM forming process to achieve precise forming of the material, which is conducive to the preparation of a composite blade with excellent performance. By doping Ti2AlNb, the high-temperature tensile strength and yield strength of the composite blade are better than those of the undoped sample. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is a flowchart of a method for preparing a Ti2AlNb / Ti-48Al-2Cr-2Nb composite blade according to a specific embodiment of the present disclosure;

[0025] Figure 2 The microstructure morphology of the sample doped with 10wt.% Ti2AlNb of Example 1 of the present disclosure;

[0026] Figure 3 The phase distribution of the sample doped with 10 wt.% Ti2AlNb of Example 1 of the present disclosure;

[0027] Figure 4 is the room temperature tensile stress-strain curve of the sample doped with 10 wt.% Ti2AlNb of Example 1 of the present disclosure;

[0028] Figure 5 is a high temperature tensile stress-strain curve of the sample doped with 10wt.% Ti2AlNb according to Example 1 of the present disclosure;

[0029] Figure 6 The microstructure morphology of the sample doped with 20wt.% Ti2AlNb of Example 2 of the present disclosure;

[0030] Figure 7 The phase distribution of the sample doped with 20wt.% Ti2AlNb of Example 2 of the present disclosure;

[0031] Figure 8 is a room temperature tensile stress-strain curve of a sample doped with 20 wt.% Ti2AlNb according to Example 2 of the present disclosure;

[0032] Fig. 9 is a high temperature tensile stress-strain curve of a sample doped with 20 wt.% Ti2AlNb according to Example 2 of the present disclosure;

[0033] Fig.10 The microstructure morphology of the sample doped with 30wt.% Ti2AlNb of Example 3 of the present disclosure;

[0034] Fig.11 The phase distribution of the sample doped with 30wt.% Ti2AlNb of Example 3 of the present disclosure;

[0035] Fig.12 is a room temperature tensile stress-strain curve of a sample doped with 30 wt.% Ti2AlNb according to Example 3 of the present disclosure;

[0036] Fig.13 is a high temperature tensile stress-strain curve of the sample doped with 30wt.% Ti2AlNb according to Example 3 of the present disclosure;

[0037] Fig.14 This is a metallographic photograph of the EBM-formed Ti-48Al-2Cr-2Nb alloy of Comparative Example 1 of the present disclosure;

[0038] Fig.15 Phase distribution of different regions of the EBM-formed Ti-48Al-2Cr-2Nb alloy of Comparative Example 1 of the present disclosure; wherein, (a) the upper part, (b) the middle part, and (c) the lower part;

[0039] Fig.16The tensile stress-strain curves of the EBM-formed Ti-48Al-2Cr-2Nb alloy of comparative example 1 of the present disclosure include: (a) longitudinal tensile curve at room temperature; (b) transverse tensile curve at room temperature; (c) longitudinal tensile curve at 650°C; and (d) transverse tensile curve at 650°C. DETAILED DESCRIPTION

[0040] In order to enable those skilled in the art to better understand the technical solution of the present disclosure, the present disclosure is further described in detail below in conjunction with the accompanying drawings and specific implementation methods. It should be understood that the specific embodiments described herein are only used to explain the present disclosure and are part of the embodiments of the present disclosure, rather than all of the embodiments. Based on the embodiments of the present disclosure, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present disclosure.

[0041] like Figure 1 As shown, in one aspect of the present disclosure, a method S100 for preparing a Ti2AlNb / Ti-48Al-2Cr-2Nb composite blade is provided, which specifically comprises the following steps S110 to S130:

[0042] S110. The rotating electrode powder making method is used to prepare Ti-48Al-2Cr-2Nb powder and Ti2AlNb powder through the integrated control technology of oxygen content in the whole process.

[0043] Specifically, high-purity Ti, Al, Cr, and Nb metal raw materials are selected to ensure the purity of the final powder, the raw materials are prepared according to the corresponding atomic ratio, and the raw materials are dried to remove impurities such as moisture adsorbed on the surface of the raw materials to avoid the introduction of additional oxygen in the subsequent preparation process; then, the raw materials are placed in a water-cooled copper crucible by induction melting in a water-cooled copper crucible, and two consumable meltings and one induction melting are carried out under vacuum or high-purity inert gas (such as argon) protection to prevent the metal from reacting with oxygen in the air. The melting temperature is generally 1700-1900°C; during the melting process, the alloy composition is homogenized by stirring and other means to ensure that each element is evenly distributed in the alloy. After smelting, high-speed centrifugal casting is used to prepare highly clean and homogeneous Ti-48Al-2Cr-2Nb alloy cast rods and Ti2AlNb alloy cast rods, and the alloy cast rods obtained by smelting are fine-turned to be processed into alloy electrode round rods that meet the requirements; Ti-48Al-2Cr-2Nb powder and Ti2AlNb powder are prepared by rotary plasma powder making equipment, wherein, during the powder making process, the rotating control shaft is controlled to drive the alloy electrode round rod to rotate at a speed of 3000-50000rpm, and under the condition of argon protection, the oxygen content of the prepared powder is controlled below 700ppm.

[0044] In some preferred embodiments, the prepared Ti-48Al-2Cr-2Nb powder and Ti2AlNb powder are spherical, and the particle size range is 50-106 μm.

[0045] This embodiment uses an integrated oxygen content control technology to strictly control the oxygen content, effectively avoiding the brittle phase caused by excessive oxygen content, and significantly improving the mechanical properties of the material, such as strength and toughness.

[0046] S120. Use a powder mixing device to evenly mix the Ti-48Al-2Cr-2Nb powder and the Ti2AlNb powder to form a mixed powder.

[0047] In some preferred embodiments, the mass ratio of Ti2A1Nb powder to Ti-48Al-2Cr-2Nb powder is (10-30):(70-90). For example, 10:90, 20:80, 30:70, etc. That is, the doping amount of Ti2A1Nb powder is 10-30%.

[0048] S130, using EBM forming process, the mixed powder is formed into Ti2AlNb / Ti-48Al-2Cr-2Nb composite blade.

[0049] Specifically, the vacuum forming chamber maintains a vacuum degree of no more than 5×10 -2 Pa, preheat the substrate with an electron beam, the preheating temperature reaches 1000-1150°C, and the preheating time is 10-30min; then, the mixed powder formed in step S120 is spread layer by layer on the substrate; the mixed powder is heated by an electron beam, and under the conditions of temperature gradient control and real-time dynamic heat compensation, the printing temperature is controlled to be 1250-1350°C for 1-3h, and the spread mixed powder is selectively melted by electron beam layer-by-layer scanning according to the cross-sectional information of the blade to form a cladding layer; the cladding layer is observed in real time by an electron microscope, and the process is adjusted in real time to the defective parts of the cladding layer to realize the compensation printing repair of the cladding layer, and then the defect-free cladding layer is subjected to conformal heat treatment; the powder is spread layer by layer on the substrate and the mixed powder is clad repeatedly to form a multi-layer cladding layer, that is, a Ti2AlNb / Ti-48Al-2Cr-2Nb composite material blade print workpiece is obtained, and it is further machined to obtain a finished blade.

[0050] In some preferred embodiments, the preheating temperature of the substrate is preferably 1000°C, 1050°C, 1100°C, 1150°C, etc., and the preheating time is preferably 10 min, 20 min, 30 min, etc. Preheating the substrate can make the alloy tough and plastic during the forming process, while reducing thermal stress and preventing the generation of thermal cracks. In addition, preheating the substrate can also ensure that the initial powder layer is slightly melted, and the "powder blowing" phenomenon will not occur due to the impact of the electron beam.

[0051] In other preferred embodiments, the printing temperature may be preferably 1250°C, 1300°C, 1350°C, and the time may be preferably 1h, 2h, 3h, etc. In the melting process of the mixed powder, the scanning path is 45°, the scanning path rotates 90° between each layer, the electron beam current is preferably 12.5-14.5mA, for example, 12.5mA, 13mA, 13.5mA, 14mA, 14.5mA, etc. may be further preferred, and the scanning speed is preferably 3.5-4.5m / s, for example, 3.5m / s, 4.0m / s, 4.5m / s, etc. The thickness of the mixed powder single-layer cladding layer is 40-60μm, and the thickness of the scanning layer is 40-60μm.

[0052] In electron beam melting (EBM) forming, by using temperature gradient control and real-time dynamic heat compensation to control the printing temperature, it is possible to ensure that the melting temperature conditions of each layer of cladding powder are close, thereby ensuring the consistency of the structure, making the heating and cooling of each part of the cladding layer more uniform, and avoiding the thermal stress caused by excessive local temperature changes. Real-time dynamic heat compensation can adjust the heat input in time according to the actual temperature of the blade, further reducing the generation of thermal stress, which helps to prevent defects such as deformation and cracks in the blade and improve the dimensional accuracy and shape accuracy of the blade. Secondly, through precise temperature gradient control and real-time dynamic heat compensation, the melting and solidification process of the powder can be optimized. Appropriate temperature conditions can make the powder fully melt and fill it into each pore, reduce pore defects caused by incomplete melting of the powder or solidification shrinkage, and improve the density of the blade. Furthermore, a reasonable temperature gradient can form a larger temperature difference during the solidification process, thereby producing a higher cooling rate. According to solidification theory, a higher cooling rate is conducive to grain refinement. Real-time dynamic heat compensation can ensure the stability of the cooling rate during the entire molding process and further promote grain refinement. Refined grains can improve the strength, toughness and other mechanical properties of the material.

[0053] In addition, in electron beam melting (EBM) forming, this embodiment adopts conformal heat treatment, which can adjust the heat treatment process parameters in real time during or after the forming process to achieve precise control of the microstructure and performance of the parts, optimize the grain structure, promote phase transformation, reduce deformation and residual stress, reduce the cooling rate of the solidified layer, avoid the formation of temperature gradient differences, and promote the stability of the powder layer when the powder is spread next time, without the need for post-processing and other processes.

[0054] The sample obtained in this embodiment has high mechanical properties and good room temperature plasticity, especially when the sample surface is about 90° to the construction direction. It will present a uniform tissue morphology along the forming direction, which can effectively fuse the two powders and achieve precise forming of the material, which is conducive to the preparation of composite blades with excellent performance.

[0055] In another aspect of the present disclosure, a Ti2AlNb / Ti-48Al-2Cr-2Nb composite blade is provided. The preparation process of the blade is described above and will not be repeated here.

[0056] In this embodiment, the room temperature transverse tensile strength of the Ti2AlNb / Ti-48Al-2Cr-2Nb composite material blade obtained based on the preparation method given above is 806-939.5 MPa, the room temperature longitudinal tensile strength is 695-790.1 MPa, the high temperature transverse tensile strength is 690-876.4 MPa, and the high temperature longitudinal tensile strength is 670-791.9 MPa. At the same time, the density of the Ti2AlNb / Ti-48Al-2Cr-2Nb composite material blade obtained in this embodiment is also relatively high.

[0057] The preparation method of the Ti2AlNb / Ti-48Al-2Cr-2Nb composite blade will be further described below in conjunction with specific examples:

[0058] Example 1

[0059] This example provides a method for preparing a Ti2AlNb / Ti-48Al-2Cr-2Nb composite blade, including the following steps:

[0060] S1. The rotating electrode powder making method was used to prepare Ti-48Al-2Cr-2Nb powder and Ti2AlNb powder respectively through the whole process oxygen content integrated control technology. Among them, the oxygen content of Ti-48Al-2Cr-2Nb powder and Ti2AlNb powder was 670ppm, and the particle size range of Ti-48Al-2Cr-2Nb powder and Ti2AlNb powder was 50-105μm.

[0061] S2. A powder mixing device is used to mix Ti-48Al-2Cr-2Nb powder and Ti2AlNb powder to form a mixed powder, wherein the content ratio of Ti-48Al-2Cr-2Nb powder to Ti2AlNb powder is 90:10 respectively.

[0062] S3. The mixed powder is clad by EBM forming process to form a printed workpiece, and the Ti2AlNb / Ti-48Al-2Cr-2Nb composite blade is obtained by machining.

[0063] Specifically, the vacuum degree in the vacuum forming chamber is maintained at no more than 5×10 -2 Pa, preheat the substrate with an electron beam, the preheating temperature is 1000℃, the preheating time is 10min, the mixed powder is coated on the substrate, the mixed powder is heated by an electron beam, and the printing temperature is controlled to be 1250℃ under the conditions of temperature gradient control and real-time dynamic heat compensation, the time is 1h, the scanning path is 45°, the scanning path rotates 90° between each layer, the electron beam current is 12.5mA, 13.5mA, 14.5mA, respectively, the scanning speed is 3.5m / s, 4m / s, 4.5m / s, respectively, the powder layer height of the cladding layer is 50μm, and a cladding layer is melted to form a cladding layer. The cladding layer is observed in real time by an electron microscope, and the process is adjusted in real time for the defective parts of the cladding layer, and then the defect-free cladding layer is subjected to conformal heat treatment. The mixed powder is repeatedly clad on the substrate to form a printed workpiece, and the printed workpiece is further machined to obtain a Ti2AlNb / Ti-48Al-2Cr-2Nb blade.

[0064] As shown in Table 1, when the electron beam current is 12.5 mA and the scanning speed is 3.5 m / s, the leaf density is 4.075 g / cm 3 , the density is 99.5%. When the electron beam current is 12.5mA and the scanning speed is 4m / s, the leaf density is 3.970g / cm 3 , the density is 96.8%. When the electron beam current is 12.5mA and the scanning speed is 4.5 / s, the leaf density is 4.011g / cm 3 , the density is 97.8%.

[0065] Further, referring to Table 1, when the electron beam current is 13.5 mA and the scanning speed is 3.5 m / s, the leaf density is 4.087 g / cm 3 , the density is 99.6%. When the electron beam current is 13.5mA and the scanning speed is 4m / s, the leaf density is 4.061g / cm 3, the density is 99.0%. When the electron beam current is 13.5mA and the scanning speed is 4.5m / s, the leaf density is 4.078g / cm 3 , the density is 99.4%.

[0066] Further, please refer to Table 1. When the electron beam current is 14.5 mA and the scanning speed is 3.5 m / s, the leaf density is 4.015 g / cm 3 The density is 97.9%. When the electron beam current is 14.5 mA and the scanning speed is 4 m / s, the leaf density is 3.984 g / cm 3 , the density is 97.1%. When the electron beam current is 14.5mA and the scanning speed is 4.5m / s, the leaf density is 3.945g / cm 3 , the density is 96.2%.

[0067] According to the density and compactness of the samples obtained under the above-mentioned different parameters, the density of the samples obtained under the process conditions given in this embodiment is relatively high, especially when the electron beam current is 12.5mA and 13.5mA and the scanning speed is 3.5m / s, the density is relatively high, which is 99.5% and 99.6% respectively.

[0068] Furthermore, this embodiment takes a sample formed with an electron beam current of 12.5 mA and a scanning speed of 3.5 m / s as an example to analyze the microstructure morphology, phase distribution and tensile stress-strain curve of the composite material blade.

[0069] like Figure 2 As shown, the microstructure of the sample presents fine equiaxed structure and lamellar structure, and large white bright bands are interspersed between the fine equiaxed structure and lamellar structure.

[0070] like Figure 3 As shown in Table 2, the composite blade specimen is mainly composed of γ phase, α2 phase, B2 phase and O phase, mainly γ phase, the organization is finer and the coarse strip-like organization is less and finer.

[0071] like Figure 4 As shown, the room temperature mechanical properties of the composite blade specimens are as follows: the average tensile strength of the transverse specimen is 909.3 MPa, and the average elongation is 0.78%; the average tensile strength of the longitudinal specimen is 871.1 MPa, and the average elongation is 0.65%. Its room temperature tensile strength and yield strength are good.

[0072] like Figure 5As shown in the figure, at a high temperature of 650°C, the high-temperature mechanical properties of the composite blade specimens are as follows: the average tensile strength of the transverse specimen is 796.9 MPa, and the average elongation is 1.4%; the average tensile strength of the longitudinal specimen is 801.2 MPa, and the average elongation is 1.27%.

[0073] Example 2

[0074] This example provides a method for preparing a Ti2AlNb / Ti-48Al-2Cr-2Nb composite blade, including the following steps:

[0075] S1. The rotating electrode powder making method was used to prepare Ti-48Al-2Cr-2Nb powder and Ti2AlNb powder respectively through the whole process oxygen content integrated control technology. Among them, the oxygen content of Ti-48Al-2Cr-2Nb powder and Ti2AlNb powder was 670ppm, and the particle size range of Ti-48Al-2Cr-2Nb powder and Ti2AlNb powder was 50-105μm.

[0076] S2. A powder mixing device is used to mix Ti-48Al-2Cr-2Nb powder and Ti2AlNb powder to form a mixed powder, wherein the content ratio of Ti-48Al-2Cr-2Nb powder to Ti2AlNb powder is 80:20 respectively.

[0077] S3. The mixed powder is clad by EBM forming process to form a printed workpiece, and the Ti2AlNb / Ti-48Al-2Cr-2Nb composite blade is obtained by machining.

[0078] Specifically, the vacuum degree in the vacuum forming chamber is maintained at no more than 5×10 -2 Pa, preheat the substrate with an electron beam, the preheating temperature is 1000℃, the preheating time is 10min, the mixed powder is coated on the substrate, the mixed powder is heated by an electron beam, and the printing temperature is controlled to be 1250℃ under the conditions of temperature gradient control and real-time dynamic heat compensation, the time is 1h, the scanning path is 45°, the scanning path rotates 90° between each layer, the electron beam current is 12.5mA, 13.5mA, 14.5mA, respectively, the scanning speed is 3.5m / s, 4m / s, 4.5m / s, respectively, the powder layer height of the cladding layer is 50μm, and a cladding layer is melted to form a cladding layer. The cladding layer is observed in real time by an electron microscope, and the process is adjusted in real time for the defective parts of the cladding layer, and then the defect-free cladding layer is subjected to conformal heat treatment. The mixed powder is repeatedly clad on the substrate to form a printed workpiece, and the printed workpiece is further machined to obtain a Ti2AlNb / Ti-48Al-2Cr-2Nb composite blade.

[0079] As shown in Table 1, when the electron beam current is 12.5 mA and the scanning speed is 3.5 m / s, the leaf density is 4.134 g / cm 3 , the density is 97.9%. When the electron beam current is 12.5mA and the scanning speed is 4m / s, the leaf density is 4.109g / cm 3 The density is 97.38%. When the electron beam current is 12.5 mA and the scanning speed is 4.5 / s, the leaf density is 4.155 g / cm 3 , the density is 98.4%.

[0080] Further, referring to Table 1, when the electron beam current is 13.5 mA and the scanning speed is 3.5 m / s, the leaf density is 4.169 g / cm 3 , the density is 98.7%. When the electron beam current is 13.5mA and the scanning speed is 4m / s, the leaf density is 4.177g / cm 3 , the density is 98.9%. When the electron beam current is 13.5mA and the scanning speed is 4.5m / s, the leaf density is 4.098g / cm 3 , the density is 97.0%.

[0081] Further, please refer to Table 1. When the electron beam current is 14.5 mA and the scanning speed is 3.5 m / s, the leaf density is 4.088 g / cm 3 , the density is 96.8%. When the electron beam current is 14.5mA and the scanning speed is 4m / s, the leaf density is 4.161g / cm 3 , the density is 98.5%. When the electron beam current is 14.5mA and the scanning speed is 4.5m / s, the leaf density is 4.089g / cm 3 , the density is 96.8%.

[0082] According to the density and compactness of the samples obtained under the above-mentioned different parameters, it can be known that the density of the samples obtained under the process conditions given in this embodiment is relatively high, especially when the electron beam current is 12.5mA, the scanning speed is 4.5m / s, the electron beam current is 13.5mA, the scanning speed is 3.5m / s, the electron beam current is 13.5mA, the scanning speed is 4m / s, and the electron beam current is 14.5mA, and the scanning speed is 4m / a, the density of each sample formed is above 98%.

[0083] Furthermore, this embodiment takes a sample formed with an electron beam current of 14.5 mA and a scanning speed of 4 m / a as an example to analyze the microstructure morphology, phase distribution and tensile stress-strain curve of the composite material blade.

[0084] like Figure 6 As shown, the tissue morphology of the above composite blade sample has a significant change compared with the undoped sample and the sample of Example 1. It becomes mainly composed of needle-shaped tissue and large lamellar tissue, and the equiaxed tissue is distributed between adjacent needle-shaped or lamellar tissues. The white bright band becomes smaller and is evenly distributed in the lamellar tissue. The average grain size increases to 65μm, and the band-shaped tissue disappears, replaced by large lamellar clusters.

[0085] like Figure 7 As shown in Table 2, compared with Example 1, the phase composition of the composite blade sample did not change, but the content of the γ phase was significantly reduced. The phase content of the composite blade sample doped with 20wt.% Ti2AlNb is shown in Table 2. The α2 phase and B2 phase continue to increase, and the B2 phase and α2 phase are evenly distributed in the γ phase. Figure 7 It can be seen that the O phase mostly exists in the B2 phase and the α2 phase, and less exists alone in the γ phase, which is related to the phase transformation of Ti2AlNb powder during the EBM forming process.

[0086] like Figure 8 As shown, the room temperature mechanical properties of the composite blade specimens are as follows: the average tensile strength of the transverse specimen is 939.5 MPa, and the average elongation is 0.82%; the average tensile strength of the longitudinal specimen is 790.1 MPa, and the average elongation is 0.66%.

[0087] like Fig. 9 As shown, the high temperature (650°C) mechanical properties of the composite blade specimens are as follows: the average tensile strength of the transverse specimen is 876.4 MPa, and the average elongation is 2.3%; the average tensile strength of the longitudinal specimen is 791.9 MPa, and the average elongation is 1.6%.

[0088] Example 3

[0089] This example provides a method for preparing a Ti2AlNb / Ti-48Al-2Cr-2Nb composite blade, including the following steps:

[0090] S1. The Ti-48Al-2Cr-2Nb powder and Ti2AlNb powder were prepared by the rotating electrode powder making method through the integrated control technology of the oxygen content in the whole process. Among them, the oxygen content of the Ti-48Al-2Cr-2Nb powder and the Ti2AlNb powder was 670ppm, and the particle size range of the Ti-48Al-2Cr-2Nb powder and the Ti2AlNb powder was 50-105μm.

[0091] S2. A powder mixing device is used to mix Ti-48Al-2Cr-2Nb powder and Ti2AlNb powder to form a mixed powder, wherein the content ratio of Ti-48Al-2Cr-2Nb powder to Ti2AlNb powder is 70:30 respectively.

[0092] S3. The mixed powder is clad by EBM forming process to form a printed workpiece, and the Ti2AlNb / Ti-48Al-2Cr-2Nb composite blade is obtained by machining.

[0093] Specifically, the vacuum degree in the vacuum forming chamber is maintained at no more than 5×10 -2 Pa, preheat the substrate with an electron beam, the preheating temperature is 1000℃, the preheating time is 10min, the mixed powder is coated on the substrate, the mixed powder is heated by an electron beam, and the printing temperature is controlled to be 1250℃ under the conditions of temperature gradient control and real-time dynamic heat compensation, the time is 1h, the scanning path is 45°, the scanning path rotates 90° between each layer, the electron beam current is 12.5mA, 13.5mA, 14.5mA, respectively, the scanning speed is 3.5m / s, 4m / s, 4.5m / s, respectively, the powder layer height of the cladding layer is 50μm, and a cladding layer is melted to form a cladding layer. The cladding layer is observed in real time by an electron microscope, and the process is adjusted in real time for the defective parts of the cladding layer, and then the defect-free cladding layer is subjected to conformal heat treatment. The mixed powder is repeatedly clad on the substrate to form a printed workpiece, and the printed workpiece is further machined to obtain a Ti2AlNb / Ti-48Al-2Cr-2Nb blade.

[0094] As shown in Table 1, when the electron beam current is 12.5 mA and the scanning speed is 3.5 m / s, the leaf density is 4.278 g / cm 3 , the density is 98.4%. When the electron beam current is 12.5mA and the scanning speed is 4m / s, the leaf density is 4.184g / cm 3 , the density is 96.3%. When the electron beam current is 12.5mA and the scanning speed is 4.5 / s, the leaf density is 4.221g / cm 3 , the density is 97.1%.

[0095] Further, referring to Table 1, when the electron beam current is 13.5 mA and the scanning speed is 3.5 m / s, the leaf density is 4.219 g / cm 3 The density is 97.0%. When the electron beam current is 13.5 mA and the scanning speed is 4 m / s, the leaf density is 4.225 g / cm 3The density is 97.2%. When the electron beam current is 13.5 mA and the scanning speed is 4.5 m / s, the leaf density is 4.277 g / cm 3 , the density is 98.4%.

[0096] Further, please refer to Table 1. When the electron beam current is 14.5 mA and the scanning speed is 3.5 m / s, the leaf density is 4.221 g / cm 3 The density is 97.1%. When the electron beam current is 14.5 mA and the scanning speed is 4 m / s, the leaf density is 4.271 g / cm 3 , the density is 98.3%. When the electron beam current is 14.5mA and the scanning speed is 4.5m / s, the leaf density is 4.268g / cm 3 , the density is 98.2%.

[0097] According to the density and compactness of the samples obtained under the above-mentioned different parameters, it can be known that the density of the samples obtained under the process conditions given in this embodiment is relatively high, especially when the electron beam current is 12.5mA, the scanning speed is 3.5m / s, and when the electron beam current is 13.5mA, and the scanning speed is 4.5m / s, the density of each sample is the highest, which is 98.4%.

[0098] Furthermore, this embodiment takes a sample formed with an electron beam current of 12.5 mA and a scanning speed of 3.5 m / s as an example to analyze the microstructure morphology, phase distribution and tensile stress-strain curve of the composite material blade.

[0099] like Fig.10 As shown, compared with Examples 1 and 2, the average grain size of the composite blade sample increases to more than 200 μm, and the white bright band increases relative to the composite blade sample doped with 20 wt.% Ti2AlNb in Example 2.

[0100] like Fig.11 As shown in Table 2, the γ phase of the composite blade specimen is further reduced. The specimen is based on the B2 phase, the α2 phase is distributed in the B2 phase matrix in a dendritic manner, and the γ phase is distributed between the "branches" of the dendritic α2 phase. The O phase is dispersed in the B2 phase matrix and the dendritic α2 phase, and is still very small in the γ phase.

[0101] like Fig.12 As shown, the room temperature mechanical properties of the composite blade specimens are as follows: the average tensile strength of the transverse specimen is 851.1 MPa, and the average elongation is 0.59%; the average tensile strength of the longitudinal specimen is 673.9 MPa, and the average elongation is 0.48%.

[0102] like Fig.13As shown, the high temperature (650°C) mechanical properties of the composite blade specimens are as follows: the average tensile strength of the transverse specimen is 941.1 MPa, and the average elongation is 3.3%; the average tensile strength of the longitudinal specimen is 803.7 MPa, and the average elongation is 2.1%.

[0103] Comparative Example 1

[0104] This example provides a method for preparing a Ti-48Al-2Cr-2Nb blade, including the following steps:

[0105] S1. The Ti-48Al-2Cr-2Nb powders were prepared by rotating electrode powder making method through the whole process oxygen content integrated control technology. The oxygen content of Ti-48Al-2Cr-2Nb powder was 670ppm, and the particle size range of Ti-48Al-2Cr-2Nb powder was 50-105μm.

[0106] S2, using EBM forming process, the powder is clad to form a printed workpiece, and the Ti-48Al-2Cr-2Nb blade is obtained by machining.

[0107] Specifically, the vacuum degree in the vacuum forming chamber is maintained at no more than 5×10 -2 Pa, preheat the substrate with an electron beam, the preheating temperature is 1000℃, the preheating time is 10min, the mixed powder is coated on the substrate, the mixed powder is heated by an electron beam, and the printing temperature is controlled to be 1250℃ under the conditions of temperature gradient control and real-time dynamic heat compensation, the time is 1h, the scanning path is 45°, the scanning path rotates 90° between each layer, the electron beam current is 12.5mA, the scanning speed is 3.5m / s, the powder layer height of the cladding layer is 50μm, and a cladding layer is melted to form a cladding layer. The cladding layer is observed in real time by an electron microscope, and the process is adjusted in real time for the defective parts of the cladding layer, and then the defect-free cladding layer is subjected to conformal heat treatment. Repeat the cladding of the mixed powder on the substrate many times to form a printed workpiece, and the printed workpiece is further machined to obtain a Ti-48Al-2Cr-2Nb blade.

[0108] As shown in Table 1, the leaf density is 3.9175 g / cm 3 , the density is 97.9%.

[0109] like Fig.14 As shown, there are fine fully layered structures in the sample. Fig.14 In the middle area, coarse grains with a bimodal structure composed of fine lamellar and equiaxed crystals can be observed, and the banded structure composed of coarse lamellar structure and equiaxed crystals increases.

[0110] like Fig.15As shown in Table 3, the phase distribution of different regions of the EBM-formed Ti-48Al-2Cr-2Nb alloy is given. The phase contents of different regions of the EBM-formed Ti-48Al-2Cr-2Nb alloy are shown in Table 3. The lower part of the EBM-formed Ti-48Al-2Cr-2Nb alloy contains more B2 phase than the upper and middle parts.

[0111] like Fig.16 As shown in the figure, the average tensile strength of the EBM-formed Ti-48Al-2Cr-2Nb alloy parallel to the forming direction (longitudinal direction) at room temperature is 695.29MPa, but the elongation is very low. This is due to the brittle characteristics of the B2 phase at room temperature and the coarsening of the structure, which leads to poor elongation. The average tensile strength perpendicular to the forming direction (transverse direction) is 806.05MPa, and the average elongation is 2.10%. At high temperature (650℃), the average tensile strength parallel to the forming direction (longitudinal direction) is 670.63MPa, and the average elongation is 4.28%. The average tensile strength perpendicular to the forming direction (transverse direction) at high temperature is 690.30MPa, and the average elongation is 3.77%. At high temperature, the softening of the dual-state structure leads to a decrease in the anisotropy of the tensile properties in the tensile direction, that is, at 650℃, the difference in properties between the longitudinal and transverse directions is small.

[0112] In summary, according to Examples 1-3 and Comparative Example 1, due to the unique formation mechanism of the O phase, the O phase will only be formed in the B2 phase and the α2 phase during the EBM forming process of the material added with Ti2AlNb powder. Since the contents of B2 phase and α2 phase formed in the original matrix Ti-48Al-2Cr-2Nb powder during the EBM forming process are very small, the distribution of the O phase in the Ti2AlNb / Ti-48Al-2Cr-2Nb composite material is mainly distributed in the B2 phase and the α2 phase, and the original matrix Ti-48Al-2Cr-2Nb powder is very little distributed in the γ phase after EBM forming.

[0113] Secondly, compared with the blade samples without Ti2AlNb doping, the tensile strength of the composite blade samples doped with Ti2AlNb has been improved both in the horizontal and vertical directions. This is because the addition of Ti2AlNb powder increases the content of α2 phase and O phase in the composite material, thereby increasing the tensile strength of the composite material. However, it can be found that the elongation of the doped sample is lower than that of the undoped sample, which is related to the B2 phase introduced by the doped Ti2AlNb powder after EBM forming. Moreover, the elongation and tensile strength of the sample doped with 20wt.% Ti2AlNb are higher than those of the samples doped with 10wt.% Ti2AlNb and 30wt.% Ti2AlNb. This is also related to the grain size. When 10wt.% Ti2AlNb is doped, the coarse γ band still exists, and there is a very obvious B2 phase segregation. When 20wt.% Ti2AlNb is doped, the γ band disappears, and the segregation of the B2 phase is significantly reduced compared with the samples with 10wt.% and 20wt.% doping amounts. When the structure is transformed into a needle-like structure, the structure of the sample doped with 20wt.% Ti2AlNb is finer than that of the sample doped with 30wt.%. Therefore, at room temperature, the composite blade doped with 20wt.% Ti2AlNb has the highest tensile strength and elongation due to its uniform structure and relatively fine grains.

[0114] Furthermore, the high temperature tensile properties of the composite blade samples formed by the three doping amounts further increase the tensile strength compared to the undoped samples, and with the increase of the doping amount, the high temperature tensile strength and elongation both increase, and after adding Ti2AlNb, the sample shows an obvious yield stage, which shows that under high temperature conditions, the plasticity of the sample increases with the increase of the doping amount. The tensile strength, yield strength and elongation of the sample doped with 30wt.% Ti2AlNb at high temperature are higher than those of other doping amounts, which is related to the phase composition of the sample doped with 30wt.%. At this time, the B2 phase content in the phase composition of the sample is the highest. Due to the large number of slip twins in the B2 phase, the slip twin activity will increase under high temperature conditions, making the B2 phase become a plastic phase, and the γ phase and O phase with higher plasticity are evenly distributed, so that the plasticity of the sample is greatly improved. Compared with the undoped sample which is mainly composed of plastic γ phase, the composite blade sample doped with 30wt.% Ti2AlNb has high α2 phase and O phase content. Both phases have higher strength than the γ phase at 650℃. Therefore, although the plasticity is not as good as that of the undoped γ-TiAl alloy, the tensile strength at high temperature is increased by 36% compared with the undoped sample.

[0115] Table 1 Density and compactness results of leaf samples under different process parameters of Examples 1-3

[0116]

[0117] Table 2 Phase content of leaves under different process parameters of Examples 1-3

[0118]

[0119] Table 3 Phase contents in different regions of Ti-48Al-2Cr-2Nb alloy formed by EBM in Comparative Example 1

[0120]

[0121] The present disclosure proposes a Ti2AlNb / Ti-48Al-2Cr-2Nb composite blade and a preparation method thereof, which have the following beneficial effects compared with the prior art: the present disclosure forms a composite blade by doping Ti2AlNb into Ti-48Al-2Cr-2Nb through an EBM forming process, thereby effectively improving the surface quality, microstructure, density and high-temperature performance of the sample, especially when the sample surface is about 90° to the construction direction, a uniform tissue morphology can be presented along the forming direction, and the mechanical properties are effectively improved. In addition, by optimizing the process, the powder blowing phenomenon can be reduced and the loss of Al element and other problems can be avoided.

[0122] It is to be understood that the above embodiments are merely exemplary embodiments used to illustrate the principles of the present disclosure, but the present disclosure is not limited thereto. For those of ordinary skill in the art, various modifications and improvements can be made without departing from the spirit and substance of the present disclosure, and these modifications and improvements are also considered to be within the scope of protection of the present disclosure.

Claims

1. A method for preparing a Ti2AlNb / Ti-48Al-2Cr-2Nb composite blade, characterized in that: The preparation method comprises: The rotating electrode powder making method was used to prepare Ti-48Al-2Cr-2Nb powder and Ti2AlNb powder respectively through the integrated control technology of oxygen content in the whole process; The Ti-48Al-2Cr-2Nb powder and the Ti2AlNb powder are uniformly mixed to obtain a mixed powder; The mixed powder is spread layer by layer on a substrate by adopting an EBM forming process, and the mixed powder is melted by electron beam scanning layer by layer to obtain a Ti2AlNb / Ti-48Al-2Cr-2Nb composite material blade.

2. The preparation method according to claim 1, characterized in that: The oxygen content of the Ti-48Al-2Cr-2Nb powder and the Ti2AlNb powder is less than 700 ppm; and / or, The Ti-48Al-2Cr-2Nb powder and the Ti2AlNb powder are spherical, and the particle size ranges from 15 to 150 μm.

3. The preparation method according to claim 1, characterized in that: The mass ratio of the Ti2AlNb powder to the Ti-48Al-2Cr-2Nb powder is in the range of (10-30):(70-90).

4. The preparation method according to claim 1, characterized in that: The EBM forming process is adopted to lay the mixed powder layer by layer on the substrate, and the mixed powder is melted by electron beam scanning layer by layer to obtain a Ti2AlNb / Ti-48Al-2Cr-2Nb composite blade, including: The vacuum degree of the vacuum forming chamber should not exceed 5×10 -2 Pa, using electron beam to preheat the substrate and coat the mixed powder on the substrate; The mixed powder is heated by an electron beam, the printing temperature is controlled by temperature gradient control and real-time dynamic heat compensation, the mixed powder is selectively melted according to the cross-sectional information of the blade to form a cladding layer, the process is adjusted for defective parts by real-time observation of the cladding layer, and then the defect-free cladding layer is subjected to conformal heat treatment; The mixed powder is repeatedly clad layer by layer on the substrate to form a Ti2AlNb / Ti-48Al-2Cr-2Nb composite material blade.

5. The preparation method according to claim 4, characterized in that: The preheating temperature of the electron beam preheating substrate is 1000-1150°C and the time is 10-30 minutes.

6. The preparation method according to claim 4, characterized in that: In the process of melting the mixed powder by electron beam, the scanning path is 45°, the scanning path rotates 90° between each cladding layer, the electron beam current is 12.5-14.5 mA, the scanning speed is 3.5-4.5 m / s, and the thickness of the mixed powder single-layer cladding layer is 40-60 μm.

7. The preparation method according to claim 4, characterized in that: The printing temperature is 1250-1350° C. and the printing time is 1-3 hours.

8. The preparation method according to claim 4, characterized in that: The density of the Ti2AlNb / Ti-48Al-2Cr-2Nb composite material blade is 97.0-99.6%.

9. The preparation method according to any one of claims 1 to 8, characterized in that: The room temperature transverse tensile strength of the Ti2AlNb / Ti-48Al-2Cr-2Nb composite blade is 806-939.5 MPa, the room temperature longitudinal tensile strength is 695-790.1 MPa, the high temperature transverse tensile strength is 690-876.4 MPa, and the high temperature longitudinal tensile strength is 670-791.9 MPa.

10. A Ti2AlNb / Ti-48Al-2Cr-2Nb composite blade, characterized in that: The Ti2AlNb / Ti-48Al-2Cr-2Nb composite material blade is prepared by the preparation method described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Electron beam selective melting additive manufacturing method and equipment for TiAl-Ti2AlNb gradient material

    CN116079071A

  • Preparation method of bionic interpenetrating Ti2AlNb / TiAl-based composite material

    CN116921697A

  • Electron beam selective melting TiAl alloy and preparation method

    CN118513565A

  • Method for radiation-based melting or sintering

    DE102017106722A1